Average Joe : be the Silicon Valley tech genius - Livermore, Shawn (Indianapolis, IN : John Wiley & Sons, 2021)
"The book covers numerous tech entrepreneurial founders and software developers, and the exciting brands or products that they created. It goes deep on a handful of them, narrowly divulging exactly how a few software developers and startup founders created breakthrough tech products like Gmail, Dropbox, Ring, Snapchat, Bitcoin, Groupon, and more. It highlights and unpacks the general hero-worship that the media and our own minds practice about tech founders and tech entrepreneurs. This idealization of tech success can create a paradox, preventing average tech professionals from their own successful journeys. This book provides hard evidence that anyone in tech can create, and anyone on the peripheral of tech can break through to the center where innovation, creativity, and opportunity meet. The anecdotes, stories, evidence, facts, arguments, logic, principles, and techniques provided in this book have helped individuals and businesses engage in slow creation cycles, improve the morale of their development teams, and increased their delivery potential of their technology solutions overall".
Introduction -- Unpacking the tech genius archetype -- The myth of genius -- Creativity : person vs. process -- The Dropbox miracle -- The coveted, unreliable flow state -- Patterns, details, and secrets -- Make me click -- Becoming contrarian -- The science of showmanship -- Mystique -- Revisiting the myth of the tech genius.
Includes bibliographical references and index.
Keywords: High technology industries; Technological innovations; Entrepreneurship; New business enterprises; Businesspeople; Computer software developers; Success in business